2022
DOI: 10.3390/antiox11061065
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Oxidative and Antioxidant Potential with Cardiometabolic Risk Profile in the Group of 60- to 65-Year-Old Seniors from Central Poland

Abstract: Pathogenesis of cardiovascular diseases is caused by, inter alia, oxidative stress. On the other hand, cardiovascular risk factors may cause redox imbalance. The pathological pathways between those components are to be determined. In the group comprised of 300 sex-matched subjects, we evaluated a number of cardiovascular risk factors: blood pressure, body mass, lipids, glucose, homocysteine, uric acid, von Willebrand factor (vWF), VCAM-1 and ICAM-1. The presence of cardiovascular diseases and drugs for their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…The inclusion criteria were age within the range of 60 to 65 years and the consent to participate in the study. The study was approved by the Committee on the Ethics of Research in Human Experimentation at the Medical University of Lodz (RNN/648/14/KB dated 23 September 2014), and was performed according to the guidelines of the Helsinki Declaration for human research [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion criteria were age within the range of 60 to 65 years and the consent to participate in the study. The study was approved by the Committee on the Ethics of Research in Human Experimentation at the Medical University of Lodz (RNN/648/14/KB dated 23 September 2014), and was performed according to the guidelines of the Helsinki Declaration for human research [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we have reported the complex associations between oxidative/antioxidative potential and cardiometabolic risk profile, as well as between PA and cardiovascular risk factors in the population of 60–65-year-old subjects [ 33 , 34 ]. In this study, we estimate how the PA (assessed both through the profile of health behaviors and overall energy expenditure) may relate to the TAS, TOS and the variety of plasma and platelets markers of an oxidation in the population of younger seniors.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have con rmed that appropriate PA has anti-in ammatory effects [19] . It can not only reduce the circulating count of white blood cells [20] but also enhance antioxidant capacity, mitigating oxidative stress [21][22] , thereby reducing the risk factor for depression.…”
Section: Introductionmentioning
confidence: 99%
“…In a population study, Sołtysik and collaborators [ 8 ] investigate the circulating oxidant and antioxidant potential and its association with the cardiometabolic risk in ageing patients. The authors assess multiple cardiovascular risk factors as well as the total antioxidative status (TAS) and total oxidative status (TOS), identifying that TAS and TOS are largely related to modifiable cardiovascular risk factors such as body mass and are affected by drugs such as angiotensin II receptor blockers.…”
mentioning
confidence: 99%